EKSISTENSI PERADILAN ADAT DI ACEH - Aceh, Mahdi (Hunafa: Jurnal Studia Islamika, 2011)
This paper deals with the existence of customary courts in Aceh in the national judicial system. From formal-juridical perspective, the existence of customary courts is not clearly stated; however, the practices of community have indicated that most of civil disputes and criminal offenses were resolved by the customary courts in Aceh. The question relates to such issues as administration of Â Aceh Â customary courts, duties of functionaries in this customary courts, and its existence within the national judicial system. This paper shows that, although the local government of Aceh does not legally include customary court as one of the state official justices, this kind of court has been sociologically recognized in resolving disputes that occur in the society. Furthermore, the local government of Aceh has codified it in the form of qÄnÅ«n (legal code).